Managing Profound Suffering at the End-of-Life: Should expanding access to continuous deep sedation be the priority? - Kirby, Jeffrey (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2015)
This paper argues that in addressing and managing profound suffering at the end-of-life, the priority should not be the legalization of physician-assisted suicide or voluntary active euthanasia in jurisdictions where these practices are not currently available. Rather, concerted efforts should be made by society and the healthcare provider community to expand patient access to proportionate distress-relieving sedation and continuous deep sedation.